2022
DOI: 10.3390/ijerph19063646
|View full text |Cite
|
Sign up to set email alerts
|

Whether Green Finance Can Effectively Moderate the Green Technology Innovation Effect of Heterogeneous Environmental Regulation

Abstract: As an essential way to promote ecological civilization, green finance is attracting wide attention. However, whether green finance can effectivelysuccessfully regulate the green technology innovation effect of heterogeneous environmental regulations and boost green technology innovation in coordination with heterogeneous environmental regulations remains unclear. Based on the re-measurement of the green finance development index of various provinces and cities in China, this study uses the spatial Durbin model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(59 citation statements)
references
References 42 publications
0
59
0
Order By: Relevance
“…There are great differences in the level of economic development, energy utilization, economic structure, environmental regulation, R&D investment, and opening up in different regions of China, which makes the effect of green financial development on carbon emissions exhibit heterogeneity in different regions [ 22 ]. The variables selected in the existing research are different.…”
Section: Empirical Strategymentioning
confidence: 99%
“…There are great differences in the level of economic development, energy utilization, economic structure, environmental regulation, R&D investment, and opening up in different regions of China, which makes the effect of green financial development on carbon emissions exhibit heterogeneity in different regions [ 22 ]. The variables selected in the existing research are different.…”
Section: Empirical Strategymentioning
confidence: 99%
“…Feng et al proposed that financial development is an important driving force for promoting green technology innovation [20]. Fang and Shao [21] and Wang [22] reached the same conclusion in their research. Ye et al research showed that the positive effect of the finance on green development by supporting green technology innovation is significant in eastern China [6].…”
Section: Introductionmentioning
confidence: 60%
“…Specifically, under the background of the development of green finance, the funds of financial institutions are inclined to green and high-tech industries, forcing the "two high and one surplus" industries to carry out green technological innovation under the constraint of funds . At the same time, the green finance policy can not only incite the resources of financial institutions, but also incite social capital to gather in green technology innovation of enterprises, and mobilize the vitality of green technology innovation and research and development of enterprises (Fang and Shao, 2022). Second, green finance contributes to the ecological transformation of industrial structure (Hu et al, 2020).…”
Section: Baseline Resultsmentioning
confidence: 99%